Adaptation on the Key Areas of Competencies in Online Teaching Modality during the Wake of Covid-19 Pandemic - Claro, Queenne Kimverlee; Munar, Emilyn Manaligod (International Journal of Education, Science, Technology, and Engineering (IJESTE), 2022)
The purpose of this study is to assess the online teaching preparedness of the faculty staff and evaluate their key areas of competencies to better prepare teaching faculty of Higher Education Institution (HEI) specifically in Santiago City, Isabela, Philippines for an effective online teaching modality. A descriptive cross-sectional survey design was used in the study and analytical sample used was total enumeration which composed of 38 respondents from different HEI of Santiago City. Data were collected using the Faculty-Self Assessment: Preparing for Online Teaching adapted in Penn State University with total of 30 items and divided in three categories of competencies. The result found that teaching faculty was successfully done in all the key areas of competencies in online teaching (M=2.38, SD= 0.65). The findings revealed there is a significant difference in age but no significant difference on gender and educational attainment based on the level of preparedness in teaching using the online modality.